Knowledge, attitude and practice of testicular self-examination among non-health sciences male undergraduate students - Abd. Majid, Aina Fahada; Jamaludin, Iqbal; Ahmad, Azmir (IIUM Press, 2025)
Background: The incidence and late detection of testicular cancer in Malaysia are increasing with young adult as susceptible population. Testicular self-examination is a tool that can detect testicular cancer early. The practice of testicular self-examination among university students worldwide is disappointing. In Malaysia, the awareness on testicular cancer and testicular self-examination among university students is underreported. This study aimed to identify the level of knowledge, attitude and practice, and their associations among non-health sciences male undergraduate students in a university in Malaysia. Methods: A cross-sectional study was conducted among 253 eligible respondents who were recruited using stratified random sampling. A self-administered questionnaire was used to collect the knowledge, attitude and practice data on testicular cancer and testicular self-examination. The descriptive data were presented in frequency and percentage. The associations between the variables were analyzed using Chi-square test. Results: Majority of respondents have poor knowledge (53.4%), unfavorable attitude (53%) and not practicing testicular self-examination (76.7%). Chi-square test showed that these variables were significantly associated with each other (p<0.05). The analysis also showed a significant association between knowledge and history of testicular abnormalities (p<0.05), as well as practice and source of information (p<0.05). Conclusion: The study found unsatisfactory level of knowledge, attitude and practice on testicular cancer and testicular self-examination, and significant associations between these variables among non-health sciences male undergraduate students at the university. This study provides a preliminary result on the importance of promoting testicular self-examination among university students in reducing the incidence of testicular cancer